In search of the Dioskouroi: image, myth and cult - Graham, SV (2015)
This study explores the Greeks' experience of the Dioskouroi before the arrival of the Romans, stimulated by Cicero's assertion (Cic. Nat.D. 3.15(39)) that by his time they were worshipped widely in Greece, possibly more than the Olympians: from the archaeological evidence, a surprising claim. The task is complicated by the brothers' different incarnations in different places and at different times, and the variability and patchiness of the evidence for the period, from Homeric times to c. 146 BC. To address this (explained in Chapter 1), the study is designed around examining the evidence in selected locations over time, with an underlying theme of comparing the archaeological with the literary evidence, much of which is Roman. An overview of the evidence from literature, images and buildings sets the stage (Chapter 2). The association of Kastor and Polydeukes with 'Lakedaimon' in the literature, from Homer onwards, led the study to focus primarily on Sparta and the Peloponnese (Chapter 3), looking closely also at Sparta's near neighbours, Messene and Argos. It then looks at evidence from Thera, Kyrene and Naukratis (Chapter 4), in order to include some of the earliest material evidence we have of cult of the Dioskouroi in Greek settlements, which also have associations with Sparta and Lakonia; evidence from Thasos is included too. The final chapter considers the findings and assesses the usefulness of the methodology. The paucity of architectural evidence for major monuments and buildings specifically dedicated to the Dioskouroi, except in centres where Greeks gathered from different places for trade or religious reasons, may be explained if the primary location of their cult was the individual household, buildings only being needed for dedications to the brothers by Greeks away from home. It could also explain the seeming mismatch between Cicero's statement and the archaeological record.